Innovative laboratory techniques shaping cancer diagnosis and treatment in developing countries - Azeez Okikiola Lawal; Tolutope Joseph Ogunniyi; Oriire Idunnuoluwa Oludele; Oluwaloseyi Ayomipo Olorunfemi; Olalekan John Okesanya; Jerico Bautista Ogaya; Emery Manirambona; Mohamed Mustaf Ahmed; Don Eliseo Lucero-Prisno (Discover Oncology)
Abstract Cancer is a major global health challenge, with approximately 19.3 million new cases and 10 million deaths estimated by 2020. Laboratory advancements in cancer detection have transformed diagnostic capabilities, particularly through the use of biomarkers that play crucial roles in risk assessment, therapy selection, and disease monitoring. Tumor histology, single-cell technology, flow cytometry, molecular imaging, liquid biopsy, immunoassays, and molecular diagnostics have emerged as pivotal tools for cancer detection. The integration of artificial intelligence, particularly deep learning and convolutional neural networks, has enhanced the diagnostic accuracy and data analysis capabilities. However, developing countries face significant challenges including financial constraints, inadequate healthcare infrastructure, and limited access to advanced diagnostic technologies. The impact of COVID-19 has further complicated cancer management in resource-limited settings. Future research should focus on precision medicine and early cancer diagnosis through sophisticated laboratory techniques to improve prognosis and health outcomes. This review examines the evolving landscape of cancer detection, focusing on laboratory research breakthroughs and limitations in developing countries, while providing recommendations for advancing tumor diagnostics in resource-constrained environments.